IN DEFENSE OF A LIBERAL EDUCATION - Wisnu Setiadi Nugroho (Faculty of Economics and Business, Universitas Gadjah Mada, 2016)
A book review dealing with the liberal arts' importance and the critiques made on the discipline taught in academic curriculum. The followings are the data about the book:Keyword:Education, Liberal Arts, American Education SystemPublisher:W.W. Norton & Company. Inc. 2015. New YorkLength:200 pagesPrice:23.95 (hardcover)Reading rating:8 (1 = very difficult; 10 = very easy)Overall rating:3 (1 = average; 4 = outstanding)